PENERAPAN RESTORATIVE JUSTICE TERHADAP TINDAK PIDANA PENCURIAN (STUDI KASUS KEPOLISIAN RESOR PASAMANBARAT) - Hidayat, Roy; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Creating a firm, honest and consistent law enforcement attitude towards the will of law and law enforcement for Police investigators is not easy. At least a strong moral commitment is needed, to carry out the task, police investigators are given the authority of a personal nature, as mentioned in Article 7 Paragraph (1) point j and the Police Law Article 16 paragraph (1) point 1 and Article 18, which authorizes